A general framework of a Reference Model for Intelligent Integrated Manufacturing Systems (REMIMS) - ÖZTEMEL, ERCAN (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Today's highly competitive business environment forces the managers to continuously make the best decisions in the shortest possible time. The ability to provide concurrency among manufacturing functions is a critical need for modern organizations as, especially, distributed environment requires synchronization of manufacturing functions. Moreover, manufacturing companies need to have strong capability of adaptation (agility) mainly because of the dynamic relationships that must be established between manufacturing units. To achieve these, there is a need for an integrated manufacturing system that will handle all interactions and interrelationships which will then be affected by the changes and create maximum gain under limited resources. In order to create and effectively manage such an integrated manufacturing system there is a need for a reference model. In this paper, such a reference model called REference Model for intelligent Integrated Manufacturing System (REMIMS) is introduced. REMIMS has hierarchical architecture with several agents responsible for different manufacturing functions. To facilitate REMIMS and allow interaction among the agents to share their knowledge, a specific knowledge exchange protocol in a knowledge network is being developed. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Integrated manufacturing; Knowledge protocols; Knowledge networks; REMIMS; Intelligent manufacturing systems; Agents; Distributed manufacturing; Multi-agent systems; AGENT-BASED ARCHITECTURE; METAMORPH